CATERING SERVICES IN THE FIELD OF TOURISM - Abduganiyeva M (The latest news and research in education, 2025)
This paper examines the crucial role of catering services within the tourism industry. It explores the diverse range of food and beverage offerings provided to travelers, from in-room dining and restaurant services in hotels to catering for events and excursions. The analysis considers the impact of culinary trends, cultural preferences, and dietary restrictions on catering operations. Furthermore, the paper investigates the importance of hygiene, safety, and sustainability in catering services, highlighting best practices and challenges faced by providers. Finally, it discusses the evolving relationship between catering and the overall tourist experience, emphasizing the contribution of exceptional food and beverage services to overall satisfaction.